Pengaruh Event Marketing, Branding dan Kualitas Layanan terhadap Kepuasan Pelanggan pada Momoyo Pademangan - Yani, Ari Soeti; Nathadihardja, Sukartono; Inayah, Solehah (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2025)
This study aims to maintain customer satisfaction as a benchmark for overcoming challenges such as inconsistencies in service and complaint handling, which can potentially damage a company's image. This study used a quantitative approach using purposive sampling technique. Data collected through questionnaires were analyzed using t-test, F-test, moderated regression tests, and correlation analysis. This study shows that the majority of participants gave positive evaluations of event marketing, branding, and service quality, as well as a very good level of consistency.